Meta-analysis identifies five novel loci associated with endometriosis highlighting key genes involved in hormone metabolism. - Sapkota, Y; Steinthorsdottir, V; Morris, AP; Fassbender, A; Rahmioglu, N; De Vivo, I; Buring, JE; Zhang, F; Edwards, TL; Jones, S; O, D; Peterse, D; et al. (Springer Nature, 2017)
Endometriosis is a heritable hormone-dependent gynecological disorder, associated with severe pelvic pain and reduced fertility; however, its molecular mechanisms remain largely unknown. Here we perform a meta-analysis of 11 genome-wide association case-control data sets, totalling 17,045 endometriosis cases and 191,596 controls. In addition to replicating previously reported loci, we identify five novel loci significantly associated with endometriosis risk (P<5 × 10(-8)), implicating genes involved in sex steroid hormone pathways (FN1, CCDC170, ESR1, SYNE1 and FSHB). Conditional analysis identified five secondary association signals, including two at the ESR1 locus, resulting in 19 independent single nucleotide polymorphisms (SNPs) robustly associated with endometriosis, which together explain up to 5.19% of variance in endometriosis. These results highlight novel variants in or near specific genes with important roles in sex steroid hormone signalling and function, and offer unique opportunities for more targeted functional research efforts.